Patient-Specific Synthetic Osteochondral Resurfacing of an Extensive Shoulder OCD Lesion in a Dog - Sutalo, Sanja; Kühn, Michael; Böttcher, Peter (VCOT Open, 2024)
The aim of this study was to describe template-guided implantation and clinical outcome of a patient-specific resurfacing implant for an extensive humeral head osteochondritis in a client-owned dog. An 8-month-old intact female Irish Wolfhound, weighing 45 kg, exhibiting lameness in the right thoracic limb, and diagnosed with an extensive caudocentral humeral head osteochondritis. Based on computed tomography data, an anatomically contoured patient-specific implant (Ø 25 mm) was created. The implant consisted of a trabecular titanium base and a polycarbonate urethane bearing cup. For intraoperative guidance, a surgical drill guide, models of the affected humeral head, and trial implants were 3D printed. The implantation procedure was performed using the modified Cheli approach. Orthopaedic and radiographic follow-up examinations were conducted at 6 weeks and 10 months postoperatively. The examination revealed stable implant position, and some mild residual lameness at 6 weeks. Furthermore, the mild osteophytosis, initially evident on the day of surgery, showed a progression during each subsequent follow-up. Complications were not observed at any time point. At 10 months, the dog was free of lameness and exhibited no functional impairment, even after strenuous exercise. This level of activity remained unchanged up to the latest follow-up at 18 months, as confirmed during a telephonic interview. The utilization of a patient-specific resurfacing implant using a guided approach was technically feasible and resulted in excellent short- to mid-term clinical outcome in this case of extensive caudocentral humeral head osteochondritis dissecans (OCD) lesion. However, it is crucial to note that the potential influence of the implant on osteoarthritis progression requires further investigation.
Keywords: osteochondritis dissecans; shoulder joint; resurfacing; polyurethane; patient specific; navigation; dog